Thermal challenge significantly alters gene expression in breast muscle of commercial turkey poults - Reed, Kent M.; Velleman, Sandra G.; Strasburg, Gale M. (Frontiers in Physiology, 2025)
Temperature extremes can compromise livestock welfare and pose serious threats to both economic stability and global food security. In commercial poultry production, newly hatched birds are particularly vulnerable to thermal stress, with growth-selected species such as turkeys being at heightened risk. To cope with temperature challenges, poultry undergo metabolic, physiological, and behavioral adaptations—responses that may have lasting effects on muscle development and, ultimately, meat quality. This study examined transcriptional changes in the breast muscle of young commercial turkey poults exposed to acute thermal stress. Hatchlings were brooded for 3 days at one of three temperatures: control (35 °C), cold (31 °C), or heat (39 °C). Pectoralis major muscle samples were collected, RNA extracted, and transcriptomes were analyzed via deep sequencing. Both cold and heat exposure resulted in reduced body weight compared to control poults. Both thermal stress conditions produced significant differential gene expression. In commercial birds, affected genes were involved in muscle differentiation and development, stress adaptation and apoptosis/protein turnover, energy metabolism and nutrient processing, as well as mitochondrial function and oxidative stress response. Notably, cold stress altered genes related to lipid and glucose metabolism (PDK4, ANGPTL4 and DGAT2), while heat stress affected genes (C/EBPβ and MUSTN1) were associated with differentiation and development and intracellular lipid accumulation. These findings provide a foundation for further studies into the genetic mechanisms driving physiological responses to thermal challenge in poultry.